Engaging the regime of comedy: An analysis of the representation of “blackness” and “whiteness” in Leon Schuster’s: There is Zulu on My Stoep (1993) and Mr. Bones 1 (2001). - Chaleka, Tariro Courage (Midlands State University, 2017)
This dissertation is a multimodal discourse analysis of the representation of the fact of “blackness” and “whiteness” in Leon Schuster There is a Zulu on My Stoep (1993) and Mr Bones 1 (2001). By examining the interplay of the multiple modes engaged in the regime of comedy, the study examines how the two dichotomies are represented in the film narrative of comedy. What need to be recognized is the notion that film as text is divorced of meaning. Meaning is constructed by the viewer or reader using his or her “frame of reference”. Each reader or viewer has his or her reading or viewing position. What therefore might be comedy in the film genre can be tragedy to the other. The comical representation of the two dichotomies can be regarded as a way of engaging the politics of representation which can either maintain or reinforce ideologies. It is tantamount to note that black and white notions are relatively different. The two dichotomies are based on totally different principles, to uphold whiteness and defend it is to attack and destroy blackness. As one is the opposite of the other. This is however realized in the “buddy racial films understudy”.